Civilization as a threat to human health? - Trnovec, T; Cook, T; Kahayová, K; Nyulassy, S (Central European journal of public health, 2001)
Civilization can be defined as the distinctly human attributes and attainments of a particular society. In general, the development of civilization is viewed as a positive step for the well-being of the human species, leading to an increased duration and quality of human life. The accelerated progress of civilization (mainly industrialization, urbanization and nutrition) has lead to new possibilities for adverse effects on human health. A collection of problems referred to as 'civilization diseases' has become the subject of serious concern but review of available data indicates that this concept appears to add very little to our understanding of modern environmental influences on human health. Important limitations in the continued use of this term are its non-specificity, the lack of a unifying scientific foundation, and provision of virtually no direction for remediation of these diseases or for future research. In addition, the use of this term has been localized to primarily post-socialist European countries. In view of these limitations, it seems more productive for scientists, in all parts of the world, to embrace the discipline of environmental health science and to discontinue use of the term "civilization diseases".
Keywords: Slovenská republika; průmysl; Environmental Health; Epidemiologic Studies; civilizace; Industry; Risk Assessment; Humans; lidé; environmentální zdraví; Europe; hodnocení rizik; Western World; Evropa; epidemiologické studie; Civilization; západní svět; Slovakia